EMPLOYEES: OCCUPATIONAL SELF-EFFICACY AND WORK STRESS - Prahara, Sowanya A.; Indriani, Novi (Journal of Psychology and Instruction, 2019)
This study aims to determine the relationship between occupational self-efficacy and work stress on production employees. The hypothesis is that there is a negative relationship between occupational self-efficacy and work stress on production employees. The subjects in this study amounted to 60 people who have the characteristics of production employees and have a service life of between one to six years. The sampling technique used in this study is the purposive sampling method. The data collection tool in this study uses a Likert Scale, Work Stress Scale, and Occupational Self-Efficacy Scale. The results of data analysis using the product-moment correlation test between occupational self-efficacy and work stress on production employees showed a Pearson correlation value of (R) = -0.614 with a significance of p = 0,000 (p <0.050). These results indicate that there is a significant negative relationship between occupational self-efficacy and work stress.